1994
DOI: 10.1677/joe.0.1430045
|View full text |Cite
|
Sign up to set email alerts
|

Circulating gonadotrophin surge-attenuating factor from superovulated women suppresses in vitro gonadotrophin-releasing hormone self-priming

Abstract: A perifusion system based on ovine pituitary tissue explants was used to investigate the effects of follicular fluid (hFF) and serum from superovulated women on pituitary responsiveness to gonadotrophin-releasing hormone (GnRH). The specific aims of the study were to determine both if gonadotrophin surge-attenuating factor (GnSAF) bioactivity is present in the peripheral circulation as well as in the follicles of superovulated women and if GnSAF suppresses GnRH self-priming in vitro. Two pulses of GnRH, 1 h ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…A final possibility is simply that of nonspecific protein-loading effects. Using our ovine pituitary models [22], we have shown that the same batch of superovulated serum as that used in the present study markedly suppresses ovine pituitary responsiveness to GnRH. This was seen both in the pituitary monolayer system, which includes 12.5% of sera in the buffer, and in the pituitary perifusion model, where heat-inactivated plus charcoaltreated serum from non-superovulated humans was used to control for nonspecific effects.…”
Section: Discussionmentioning
confidence: 49%
“…A final possibility is simply that of nonspecific protein-loading effects. Using our ovine pituitary models [22], we have shown that the same batch of superovulated serum as that used in the present study markedly suppresses ovine pituitary responsiveness to GnRH. This was seen both in the pituitary monolayer system, which includes 12.5% of sera in the buffer, and in the pituitary perifusion model, where heat-inactivated plus charcoaltreated serum from non-superovulated humans was used to control for nonspecific effects.…”
Section: Discussionmentioning
confidence: 49%
“…GnSIF/AFs cannot be measured directly, because its molecular structure has not been fully identified yet. GnSIF/AF normally influences LH through inhibition of the GnRH-induced LH secretion and antagonizing the self-priming effect of GnRH (35,36,37). All measurable ovarian hormones in this study did not change, thus it is not likely that GnSIF/AF would be the only ovarian hormone that would change after the manipulation.…”
Section: Ovarian Hormonesmentioning
confidence: 62%
“…This was necessary since the bioassay of 441 samples (147 individual blood samples, each at three different doses) would have been prohibitively expensive and time consuming. This approach has been used previously with samples from women and forms the basis of much of the current literature on GnSAF/IF bioactivity in biological fluids [12,31]. Performed carefully, these pools of equal volumes of plasma from equal numbers of animals yield data that correlate closely with data from all the samples assayed separately.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been attributed to the putative ovarian hormone gonadotropin surge-attenuating/inhibiting factor (GnSAF/IF) [9] and is supported by data indicating that GnSAF/IF reduces GnRH self-priming, an important component of the LH surge, both in vivo [10] and in vitro [11,12]. Treatment with FSH stimulates the production of GnSAF/IF bioactivity in vivo in humans, monkeys, and rats [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%